Battery and electric equipment
By defining the tensile strength and adhesion relationship of the fluorine-free separator, the problem of difficult control of the bonding strength between the fluorine-free separator and the electrode sheet is solved, and the comprehensive performance balance of the battery is achieved.
Patent Information
- Application Number
- CN202411995228.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
AI Technical Summary
The bonding strength between the fluorine-free separator and the electrode sheet is difficult to achieve rational control, resulting in unbalanced or missing batteries in overall performance.
By defining the tensile strength of the fluorine-free diaphragm and the relationship between the fluorine-free diaphragm and the electrode sheet, it is ensured that σm, σt, Tc, and Ta meet a specific range to establish a good interface matching.
The battery cycle performance and charge and discharge rate balance are achieved, ensuring the battery's overall performance balance.
Smart Images

Figure CN119812680A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a battery and an electrical device. Background Art
[0002] In recent years, based on environmental protection or certain industrial needs, batteries based on fluorine-free diaphragms have gradually been used in various fields.
[0003] The glue layer in the fluorine-free diaphragm is formed by coating with a fluorine-free adhesive. The setting of the glue layer makes it difficult to achieve a good match between the fluorine-free diaphragm and the electrode (which can be a positive electrode or a negative electrode). The bonding strength between the fluorine-free diaphragm and the electrode is difficult to achieve reasonable control, which can easily cause imbalance or loss in the overall performance of the battery. Summary of the invention
[0004] The present application provides a battery and an electrical device that can balance the comprehensive performance of the battery.
[0005] A first aspect of the present application provides a battery, comprising:
[0006] Positive electrode;
[0007] Negative electrode;
[0008] and a fluorine-free diaphragm, the fluorine-free diaphragm comprising a base film and adhesive layers formed on both sides of the base film, the adhesive layers comprising an adhesive agent that does not contain fluorine,
[0009] The tensile strength of the fluorine-free diaphragm in the length direction is σm, the tensile strength of the fluorine-free diaphragm in the width direction is σt, the peeling force between the fluorine-free diaphragm and the positive electrode sheet is Tc, the peeling force between the fluorine-free diaphragm and the negative electrode sheet is Ta, and the σm, the σt, the Tc, and the Ta satisfy the relationship:
[0010] 80≤(σm+σt) / Tc≤800;
[0011] 120≤(σm+σt) / Ta≤900.
[0012] According to the battery described in the first aspect of the present application, by limiting the relationship between the tensile strength of the fluorine-free diaphragm and the bonding force between the fluorine-free diaphragm and the electrode, the interface problem caused by the mismatch between the strength and thickness of the fluorine-free diaphragm and the bonding force with the electrode can be solved, and the cycle performance and charge and discharge rate of the battery can be guaranteed, thereby achieving a balance in the overall performance of the battery.
[0013] According to an embodiment of the present invention, the σm, the σt, the Tc, and the Ta satisfy the relationship:
[0014] 100≤(σm+σt) / Tc≤440;
[0015] 130≤(σm+σt) / Ta≤500.
[0016] According to one embodiment of the present invention, H0=4 μm to 15 μm;
[0017] And / or, said σm=1100kgf / cm 2 ~3000kgf / cm 2 ;
[0018] And / or, said σt=1000kgf / cm 2 ~3000kgf / cm 2 ;
[0019] And / or, Tc=6N / m-30N / m;
[0020] And / or, Ta=6N / m~30N / m.
[0021] According to one embodiment of the present invention, H0=4 μm to 9 μm;
[0022] And / or, said σm=1800kgf / cm 2 ~2800kgf / cm 2 ;
[0023] And / or, said σt=1800kgf / cm 2 ~28000kgf / cm 2 ;
[0024] And / or, Tc=8N / m-20N / m;
[0025] And / or, Ta=8N / m~15N / m.
[0026] According to one embodiment of the present invention, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer, the negative electrode sheet includes a negative electrode current collector and a negative electrode material layer, the tensile strength of the positive electrode current collector is σc, the tensile strength of the negative electrode current collector is σa, and the σc and σa satisfy the relationship:
[0027] 20≤σc / Tc+σa / Ta≤75.
[0028] According to one embodiment of the present invention, the σc=90N / m to 260N / m;
[0029] And / or, the σa=300N / m~800N / m.
[0030] According to one embodiment of the present invention, the σc=110N / m~230N / m;
[0031] And / or, the σa=350N / m~550N / m.
[0032] According to one embodiment of the present invention, the thickness of the base film is H0, the porosity of the fluorine-free separator is Ks, the porosity of the positive electrode sheet is Kc, the porosity of the negative electrode sheet is Ka, and H0, Ks, Kc, and Ka satisfy the relationship:
[0033] 0.028≤Ka / (H0+4*Ks)≤0.066;
[0034] 0.022≤Kc / (H0+4*Ks)≤0.062.
[0035] According to an embodiment of the present invention, H0=4um~15um, preferably, H0=4um~9um;
[0036] And / or, Ks=24% to 52%, preferably, Ks=34% to 45%;
[0037] And / or, Kc=14% to 44%, preferably, Kc=22% to 37%;
[0038] And / or, the Ka=19%-48%, preferably, the Ka=25%-38%.
[0039] According to one embodiment of the present invention, the thickness of the base film is H0, the fluorine-free separator further includes a ceramic layer disposed on at least one side of the base film, the thickness of the ceramic layer is H1, the negative electrode sheet extends out of the positive electrode sheet in the width direction and the length of the negative electrode sheet extending out of the positive electrode sheet is F0, the fluorine-free separator extends out of the negative electrode sheet in the width direction and the length of the fluorine-free separator extending out of the negative electrode sheet is F1, and the H0, the H1, the F0, and the F1 satisfy the relationship:
[0040] 0.18≤F0 / (H0+2*H1)≤0.38;
[0041] 0.18≤F1 / (H0+2*H1)≤0.38.
[0042] According to an embodiment of the present invention, H0=4um~15um, preferably, H0=4um~9um;
[0043] And / or, H1=0.5 μm to 3 μm;
[0044] And / or, F0=1 μm to 4 μm;
[0045] And / or, F1=1 μm to 4 μm.
[0046] According to one embodiment of the present invention, the adhesive layer is selected from one or more of polyethylene oxide, polyacrylonitrile, polymethyl methacrylate, polyvinyl butyral, polydopamine, polyimide, and polystyrene-acrylate.
[0047] A second aspect of the present application provides an electrical device, comprising the battery described in the first aspect. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the prior art, the drawings required for use in the embodiments or the prior art description are briefly introduced below. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0049] Figure 1 A cross-sectional view of a battery provided in some embodiments of the present application is shown.
[0050] Reference numerals:
[0051] 100-positive electrode sheet; 200-negative electrode sheet; 300-fluorine-free diaphragm. DETAILED DESCRIPTION
[0052] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0053] At present, the diaphragm in the battery usually has a functional coating. In order to achieve the connection between the diaphragm and the positive electrode sheet and the connection between the diaphragm and the negative electrode sheet, the functional coating is provided on both sides of the diaphragm, and a sticky adhesive layer is provided in the functional coating. The adhesive layer can usually be formed by a fluorine-containing adhesive, such as PVDF, which can improve the performance of the diaphragm to a certain extent, but the use of fluorine-containing substances and the diaphragm during the production process will cause certain pollution to the surrounding environment. In order to cope with the above phenomenon and prevent pollution to the environment, fluorine-free diaphragms and batteries formed based on the fluorine-free diaphragms came into being.
[0054] In recent years, based on environmental protection or certain industrial needs, batteries based on fluorine-free diaphragms have gradually been used in various fields. The performance of fluorine-free diaphragms is quite different from that of the above-mentioned traditional diaphragms. When batteries are made with the fluorine-free diaphragms, the specifications and parameters of the fluorine-free diaphragms themselves have an important impact on the performance of the batteries. Unlike the above-mentioned traditional diaphragms, the adhesive layer in the fluorine-free diaphragm is formed by coating with a fluorine-free adhesive. The setting of the adhesive layer of the fluorine-free diaphragm makes it difficult to achieve a good match between the fluorine-free diaphragm and the pole piece (which can be a positive pole piece or a negative pole piece). There are more serious interface problems between the fluorine-free diaphragm and the pole piece. The bonding strength between the fluorine-free diaphragm and the pole piece is difficult to achieve reasonable control, which can easily cause imbalance or loss in the overall performance of the battery. For example, when the bonding strength is low and the bonding force between the fluorine-free diaphragm and the electrode is small, poor interface contact may occur during the cycle, resulting in increased impedance, increased polarization, or lithium precipitation during the cycle, increased cycle expansion, and capacity drop, which may seriously affect the cycle life and cycle stability of the battery. It may also easily cause problems such as a decrease in ion diffusion rate that affect the charge and discharge rate of the battery. When the bonding strength is high and the bonding force between the fluorine-free diaphragm and the electrode is high, the fluorine-free diaphragm and the electrode are too tightly attached, which may easily cause poor electrolyte infiltration, greater electrode stress, and the appearance of black spots and electrode bending during the cycle, which may also affect the cycle life of the battery.
[0055] Based on this, an embodiment of the present application provides a battery, which is designed based on the specifications and parameters of a fluorine-free diaphragm and is associated with the parameters of a pole piece, so as to balance the comprehensive performance of the battery while ensuring the environmental performance of the battery.
[0056] The specifications and parameters of the fluorine-free diaphragm in the embodiment of the present application are mainly reflected in the size of the fluorine-free diaphragm, the tensile strength of the fluorine-free diaphragm and the porosity of the fluorine-free diaphragm, wherein the size of the fluorine-free diaphragm includes the thickness, length and width of the fluorine-free diaphragm, and the parameters of the pole piece in the embodiment of the present application are mainly reflected in the strength of the pole piece, the size of the pole piece and the porosity of the pole piece.
[0057] In addition, the embodiment of the present application also controls the bonding strength between the fluorine-free diaphragm and the pole piece. The bonding strength can be characterized by the peel strength between the fluorine-free diaphragm and the pole piece, and the peel strength can be reflected by the peel force between the fluorine-free diaphragm and the pole piece.
[0058] In an embodiment of the present application, the battery includes a positive electrode sheet, a negative electrode sheet and a fluorine-free separator. The positive electrode sheet, the separator and the negative electrode sheet are connected in sequence. The fluorine-free separator includes a base film and an adhesive layer formed on both sides of the base film. The adhesive layer includes a fluorine-free adhesive.
[0059] The battery can be a wound structure or a stacked structure. When the former is adopted, the positive electrode sheet, the negative electrode sheet and the fluorine-free separator are all designed to be strip-shaped structures, and the three can be wound into a wound structure along the length direction. When the latter is adopted, the positive electrode sheet, the negative electrode sheet and the fluorine-free separator can be stacked to form a stacked structure.
[0060] In the embodiment of the present application, the positive electrode sheet, the negative electrode sheet and the fluorine-free separator are arranged correspondingly, and the length direction and width direction of the three are consistent. Taking the above-mentioned winding structure as an example, the length direction is the extension direction of the strip-shaped structure, and the width direction is perpendicular to the length direction. Taking the above-mentioned stacked structure as an example, the length direction is the direction defined by the long side of the positive electrode sheet, and the width direction is the direction defined by the short side of the positive electrode sheet.
[0061] The fluorine-free diaphragm includes a base film and a functional coating disposed on both sides of the base film. The functional coating includes at least a glue layer, and the functional coating may also include a ceramic layer. When the functional coating includes a ceramic layer, the glue layer is coated on the ceramic layer.
[0062] The base film in the embodiment of the present application includes a wet film and a dry film, and the main component is one or more of PE, PP, PI, PET, and cellulose. The ceramic layer includes at least one of aluminum oxide, titanium oxide, silicon oxide, magnesium oxide, and magnesium hydroxide. The adhesive layer is selected from one or more of PEO (polyethylene oxide), PAN (polyacrylonitrile), PMMA (polymethyl methacrylate), PVB (polyvinyl butyral), PDA (polydopamine), polyimide (PI), and polystyrene-acrylate.
[0063] The tensile strength of the fluorine-free diaphragm in the length direction is σm, the tensile strength of the fluorine-free diaphragm in the width direction is σt, the peeling force between the fluorine-free diaphragm and the positive electrode sheet is Tc, and the peeling force between the fluorine-free diaphragm and the negative electrode sheet is Ta. H0, σm, σt, Tc, and Ta satisfy the relationship:
[0064] 80≤(σm+σt) / Tc≤800;
[0065] 120≤(σm+σt) / Ta≤900.
[0066] The embodiments of the present application define the relationship between the tensile strength of the fluorine-free diaphragm and the bonding force between the fluorine-free diaphragm and the electrode, which can solve the interface problem caused by the mismatch between the fluorine-free diaphragm's own strength and the bonding force between the fluorine-free diaphragm and the electrode, and can ensure the cycle performance and charge and discharge rate of the battery, thereby achieving a balance in the overall performance of the battery.
[0067] For batteries that meet the above formula range, the tensile strength of the fluorine-free diaphragm and the bonding force with the electrode are reasonably configured, which can establish a good interface with the electrode and improve the cycle performance and charge and discharge rate performance.
[0068] In the above embodiment, the tensile strength of the fluorine-free separator affects the wrapping of the electrode by the fluorine-free separator and the fixation of the active material (such as lithium ions) coated on the electrode. The above embodiment can form a suitable bonding strength by matching the above two elements.
[0069] The fluorine-free diaphragm has an important influence on the formation and performance of the battery. An important influencing factor of the diaphragm and the battery system is the bonding strength between the fluorine-free diaphragm and the pole piece, which can be characterized by the peel strength between the fluorine-free diaphragm and the pole piece, and the peel strength can be reflected by the peeling force. The interface relationship between the fluorine-free diaphragm and the pole piece is very important. The fluorine-free diaphragm is a special channel inside the battery that blocks the conduction of electrons and allows the conduction of ions. The interface between the fluorine-free diaphragm and the pole piece directly affects the battery's cycle performance, rate charge and discharge performance, etc. The fluorine-free diaphragm and the pole piece are in close contact and have good bonding strength, which can shorten the distance of charge migration, increase the migration rate, reduce the polarization of the battery, and improve the battery's rate performance. The fluorine-free diaphragm and the pole piece are in good contact, and the tensile strength of the fluorine-free diaphragm itself has a certain coating effect on the pole piece, which can prevent the active material particles of the pole piece from loosening, falling off, increasing internal resistance, and increasing polarization caused by repeated expansion and contraction during the cycle, which can improve the battery's cycle stability and cycle life. In addition, the appropriate peeling force can ensure good electrolyte infiltration and improve the battery's cycle performance.
[0070] Therefore, under the above configuration relationship, a suitable bonding strength can be formed between the fluorine-free diaphragm and the pole piece, so that good contact between the fluorine-free diaphragm and the pole piece can be achieved, thereby achieving a balance in the overall performance of the battery.
[0071] Exemplarily, (σm+σt) / Tc may be 80, 150, 200, 250, 300, 350, 400, 450, 500, 600, 700, 800, or a range consisting of any two thereof.
[0072] Exemplarily, (σm+σt) / Ta may be 120, 200, 250, 300, 350, 400, 450, 500, 600, 700, 800, 900 or a range consisting of any two thereof.
[0073] In a specific embodiment, σm, σt, Tc, and Ta satisfy the relationship:
[0074] 100≤(σm+σt) / Tc≤440;
[0075] 130≤(σm+σt) / Ta≤500.
[0076] In a specific embodiment, σm=1100 kgf / cm 2~3000kgf / cm 2 ;
[0077] and / or, σt=1000kgf / cm 2 ~3000kgf / cm 2 ;
[0078] and / or, Tc = 6 N / m to 30 N / m;
[0079] And / or, Ta=6N / m~30N / m.
[0080] The values of σm, σt, Tc, and Ta can be selected according to the above ranges to further improve the balance of the overall performance of the battery. For example, σm can be 1100 kgf / cm 2 、1500kgf / cm 2 、2000kgf / cm 2 、2100kgf / cm 2 、2260kgf / cm 2 、2500kgf / cm 2 、3000kgf / cm 2 etc., σt can be 1000kgf / cm 2 、1500kgf / cm 2 、1820kgf / cm 2 、2000kgf / cm 2 、2500kgf / cm 2 、3000kgf / cm 2 etc., Tc can be 6N / m, 7N / m, 10.2N / m, 12N / m, 18N / m, 24N / m, 30N / m, etc., and Ta can be 6N / m, 8N / m, 19.6N / m, 12N / m, 18N / m, 24N / m, 30N / m, etc.
[0081] In some more specific embodiments, σm=1800kgf / cm 2 ~2800kgf / cm 2 ;
[0082] and / or, σt=1800kgf / cm 2 ~28000kgf / cm 2 ;
[0083] and / or, Tc = 8 N / m to 15 N / m;
[0084] And / or, Ta=8N / m~20N / m.
[0085] Selecting values of σm, σt, Tc, and Ta within the above ranges can further increase the balance of the overall performance of the battery.
[0086] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer, and the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer. The positive electrode active material layer includes a positive electrode active material, a conductive agent, and a binder, and the positive electrode active material includes one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium cobalt oxide, lithium manganese oxide, and lithium iron phosphate. The negative electrode active material layer includes a negative electrode active material, a conductive agent, a thickener, and a binder, and the negative electrode active material is selected from at least one of artificial graphite, natural graphite, mesophase carbon microspheres, soft carbon, and hard carbon.
[0087] In some embodiments, the tensile strength of the positive electrode current collector is σc, the tensile strength of the negative electrode current collector is σa, and σc and σa satisfy the relationship:
[0088] 20≤σc / Tc+σa / Ta≤75.
[0089] Here, by configuring the bonding force between the fluorine-free diaphragm and the electrode, and the tensile strength of the electrode, the battery can be restrained to prevent the battery from lateral extension.
[0090] The restraint of the fluorine-free diaphragm on the lateral extension of the battery mainly relies on the bonding force between the fluorine-free diaphragm and the positive and negative electrodes. In addition, the strength of the positive and negative current collectors also affects the extension of the battery. When the strength of the positive or negative current collector is large, the extension of the electrode is more difficult, and the bonding strength of the fluorine-free diaphragm can be smaller. When the strength of the positive and negative current collectors is small, the extension of the electrode is easier, and the diaphragm needs to have a stronger bonding force to better restrain the positive and negative electrodes.
[0091] The bonding strength between the fluorine-free diaphragm and the pole piece affects the strength of the battery. After winding and injecting liquid, the positive pole piece, negative pole piece, and fluorine-free diaphragm have low strength and can still be bent and deformed. After hot pressing, the structure becomes hard and strong, and it cannot be easily bent and deformed. This is mainly due to the physical and chemical changes that occur at the interface between the fluorine-free diaphragm and the pole piece during the hot pressing process. The glue layer of the fluorine-free diaphragm and the related substances on the pole piece are fused under pressure and temperature conditions, and the strength of the entire battery is increased. Strength is an important factor affecting battery performance. Strength maintains the flatness of the battery and reduces lithium precipitation caused by internal unevenness during battery charging and discharging. At the same time, the pole piece inside the battery can remain stable, and it is not easy to have problems such as poor contact and poor electrolyte infiltration, which reduces the polarization of the battery cell. In addition, high strength can reduce the deformation of the battery. After multiple cycles, the battery has less deformation and less hard expansion, which can ensure the life of the battery.
[0092] According to the inventor's research and analysis, when the strength of the pole piece and the bonding force between the fluorine-free diaphragm and the pole piece are too small or too large, the manufacturing of the battery will be affected. Under the above configuration relationship, a reasonable balance can be achieved between the bonding force and the strength of the pole piece, thereby improving the overall performance of the battery.
[0093] Exemplarily, σc / Tc+σa / Ta may be 20, 30, 40, 50, 60, 70, 75 or a range consisting of any two thereof.
[0094] In some specific embodiments, σc=90N / m~260N / m; and / or, σa=300N / m~800N / m. Taking values of σc and σa according to the above range can further prevent the battery from lateral extension. For example, σc can be 90N / m, 120N / m, 150N / m, 180N / m, 210N / m, 220N / m, 240N / m, 260N / m, etc., and σa can be 300N / m, 400N / m, 430N / m, 500N / m, 550N / m, 600N / m, 700N / m, 800N / m, etc.
[0095] In some more specific embodiments, σc=110N / m-230N / m; and / or, σa=350N / m-550N / m.
[0096] Selecting values of σc and σa within the above range can further prevent the battery from lateral expansion.
[0097] In some embodiments, the thickness of the base film is H0, the porosity of the fluorine-free separator is Ks, the porosity of the positive electrode sheet is Kc, the porosity of the negative electrode sheet is Ka, and Ks, Kc, and Ka satisfy the relationship:
[0098] 0.028≤Ka / (H0+4*Ks)≤0.066;
[0099] 0.022≤Kc / (H0+4*Ks)≤0.062.
[0100] Here, by reasonably configuring the relationship between the porosity of the electrode, the thickness of the base film and the porosity of the fluorine-free diaphragm, the diffusion resistance of the active material can be reduced and the polarization of the battery can be prevented from increasing.
[0101] The thickness of the base film affects the overall strength of the fluorine-free separator, the wetting of the electrolyte, the transmission of active substances and the insulation.
[0102] The positive electrode active material and the negative electrode active material are coated on the corresponding positive electrode collector and the negative electrode collector in the form of particles. After rolling, there are still tiny pores between the particles. The porosity of the pole piece reflects the degree of rolling, and indirectly reflects the strength and elastic plasticity of the pole piece and the flexibility of the pole piece. In terms of the electrical performance of the battery, the pole piece with appropriate porosity has close contact between the particles, good electronic conductivity, and a certain liquid retention capacity to ensure the absorption and infiltration of the electrolyte, so that the ability of the electrolyte to penetrate from the fluorine-free diaphragm to the inside of the pole piece is enhanced. The porosity of the fluorine-free diaphragm also indirectly reflects the physical properties of the fluorine-free diaphragm, affecting the ion transmission speed and the electrolyte retention amount. At the same time, the thickness of the fluorine-free diaphragm also affects the ion transmission rate and electronic insulation of the fluorine-free diaphragm. The porosity of the pole piece and the fluorine-free diaphragm affects the flexibility and strength of the pole piece, and also affects the penetration and ion conductivity of the electrolyte.
[0103] Porosity affects the infiltration ability of the electrolyte and the ability of ion diffusion. Appropriate porosity is beneficial to improving the electrochemical performance of the battery. When the porosity of the pole piece is too large, the gap between the particles on the pole piece is larger, the pole piece compaction density is lower, and the pole piece thickness is larger, which affects the electrochemical impedance and energy density of the battery cell. At the same time, the porosity of the fluorine-free diaphragm is larger, which will also affect the K value of the battery, the constant current and constant voltage charging time, etc. When the porosity is too small, the number of active sites for ion diffusion on the pole piece is reduced, the channels for ion migration on the fluorine-free diaphragm are reduced, and the charging and discharging capacity of the battery cell is weakened, which is not conducive to high current and high power use.
[0104] Therefore, under the above configuration relationship, a reasonable balance can be achieved between the porosity of the electrode and the porosity of the fluorine-free diaphragm, so that the battery has good electrolyte permeability and ion transmission capacity, and the overall performance of the battery can be improved.
[0105] In some specific embodiments, H0=4um~15um, H0 can be 4μm, 5μm, 7μm, 10μm, 12μm, 15μm, etc. Preferably, H0=4um~9um, Ks=24%~52%, Ks can be 34%, 37%, 36.6%, 40%, 43%, 43.9%, 45%, 50% or a range composed of any two of them. Preferably, Ks=34%~45%. Kc=14%~44%, Kc can be 22%, 24%, 25%, 28%, 31%, 34%, 37% or a range consisting of any two of them, preferably, Kc=22%~37%; Ka=19%~48%, Ka can be 25%, 28%, 31%, 32.5%, 33%, 36%, 38%, 39% or a range consisting of any two of them, preferably, Ka=25%~38%.
[0106] In some embodiments, please refer to Figure 1 , the thickness of the base film is H0, the fluorine-free separator 300 further includes a ceramic layer disposed on at least one side of the base film, the thickness of the ceramic layer is H1, the negative electrode sheet 200 extends out of the positive electrode sheet 100 along the width direction and the length of the negative electrode sheet 200 extending out of the positive electrode sheet 100 is F0, the fluorine-free separator 300 extends out of the negative electrode sheet 200 along the width direction and the length of the fluorine-free separator 300 extending out of the negative electrode sheet 200 is F1. Figure 1 In the example shown, it is necessary to understand that F0 = F01 + F02, and F1 = F11 + F12. H0, H1, F0, and F1 satisfy the relationship:
[0107] 0.18≤F0 / (H0+2*H1)≤0.38;
[0108] 0.18≤F1 / (H0+2*H1)≤0.38.
[0109] Here, by configuring the relationship between the thickness of the base film and the ceramic layer, the size of the negative electrode sheet, and the size of the separator, the high-temperature stability of the battery can be improved and furnace temperature failure can be avoided.
[0110] The ceramic layer of the fluorine-free diaphragm can improve the heat resistance of the fluorine-free diaphragm and prevent the fluorine-free diaphragm from shrinking at high temperatures. The heat resistance temperature of the adhesive layer of the fluorine-free diaphragm is lower than that of the adhesive layer of the fluorine-containing diaphragm. At high temperatures, the adhesive layer is prone to viscosity failure, the adhesion between the fluorine-free diaphragm and the electrode becomes worse, and the fluorine-free diaphragm is prone to shrinkage, causing a contact short circuit between the positive electrode and the negative electrode, thereby causing battery failure. The appropriate coverage size of the fluorine-free diaphragm can prevent this phenomenon from happening.
[0111] If the thickness of the base film and ceramic layer is thin, the F0 and F1 values are small, and the battery is prone to failure at high temperatures, leading to safety problems. If the thickness of the base film and ceramic layer is thick, the F0 and F1 values are large, and the energy density of the battery is greatly reduced, which cannot meet market demand. In the above configuration relationship, the relationship between the energy density and high temperature stability of the battery can be balanced to ensure the comprehensive performance of the battery.
[0112] In some specific embodiments, H0=4um~15um, H0 can be 4μm, 5μm, 7μm, 10μm, 12μm, 15μm, etc. Preferably, H0=4um~9um, H1=0.5μm~3μm, H1 can be 0.5μm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm or a range consisting of any two of them; F0=1μm~4μm, F0 can be 1μm, 2μm, 3μm, 4μm or a range consisting of any two of them; F1=1μm~4μm, F1 can be 1μm, 2μm, 3μm, 4μm or a range consisting of any two of them.
[0113] The present application also provides an electric device, which includes the battery in the above embodiment. The present invention does not specifically limit the electric device, which can be any electric device including the battery, including but not limited to mobile phones, portable devices, laptops, electric bicycles, electric cars, electric toys, energy storage devices, etc.
[0114] The battery provided by the present invention and its application will be specifically introduced through specific embodiments below.
[0115] Unless otherwise specified, the reagents, materials and instruments used in the following examples are conventional reagents, conventional materials and conventional instruments in the art and can be obtained commercially. The reagents involved can also be synthesized by conventional methods in the art.
[0116] Example 1-1
[0117] This embodiment provides a battery, and the preparation method thereof is as follows:
[0118] 1. Preparation of positive electrode
[0119] Lithium cobalt oxide, conductive carbon black, carbon nanotubes, and PVDF are stirred into a slurry in NMP at a mass ratio of 95:1:1.5:2.5, and then coated on aluminum foil as a positive electrode collector, dried, and rolled to form a positive electrode active material layer, which is then prepared into a positive electrode sheet through cutting, welding of electrode ears, and pasting of adhesive tape. The tensile strength of the positive electrode collector is 180 N / m, and the porosity of the positive electrode sheet is 24.7%.
[0120] 2. Preparation of negative electrode sheet
[0121] CMC was dissolved in deionized water to prepare a gel, and then graphite and a conductive agent were mixed and added to the prepared gel until stirred evenly, and finally SBR was added and stirred before coating on a copper foil as a negative electrode current collector, and then baked, rolled, cut, welded to the pole ears, and taped to prepare a negative electrode sheet, the tensile strength of the negative electrode current collector was 430 N / m, and the porosity of the negative electrode sheet was 32.5%.
[0122] 3. Preparation of electrolyte
[0123] Ethylene carbonate (EC) and diethyl carbonate (DEC) were prepared into a solvent in a weight ratio of 3:7, 1 mol / L lithium hexafluorophosphate was added into the solvent, and the mixture was stirred evenly to form an electrolyte.
[0124] 4. Preparation of fluorine-free diaphragm
[0125] The polyethylene is prepared into a base film by a wet process, and the thickness of the base film is 5 μm;
[0126] Polymethyl methacrylate (PMMA) as an adhesive and sodium carboxymethyl cellulose (CMC) as a thickener are mixed in a mass ratio of 97.5:2.5, deionized water is added as a solvent, and after stirring evenly, a glue layer slurry with a solid content of 75wt% is formed;
[0127] Alumina particles of ceramic particles, styrene-butadiene rubber (SBR) as a ceramic coating binder, and deionized water as a solvent are mixed in a mass ratio of 40:10:50, and stirred evenly to form a ceramic layer slurry;
[0128] The ceramic layer slurry is coated on one surface of the base membrane and dried at 60°C to obtain a ceramic layer with a thickness of 2μm. The adhesive layer slurry is then coated on the other surface of the base membrane and the surface of the ceramic layer away from the base membrane, and dried at 60°C to obtain two adhesive layers with a thickness of 1μm. The final fluorine-free diaphragm is a 5μm base membrane + a 2μm ceramic layer (located on one side of the base membrane) + a 1μm*2 adhesive layer (located on both sides of the base membrane). The porosity of the fluorine-free diaphragm is 43.9%.
[0129] 5. Preparation of batteries
[0130] The positive electrode sheet and the negative electrode sheet are separated by a fluorine-free separator and wound into a roll core, wherein the length of the negative electrode sheet extending from the positive electrode sheet is 2 μm, and the length of the fluorine-free separator extending from the negative electrode sheet is 2 μm, and then encapsulated in an aluminum-plastic film shell, and the battery is prepared after baking, electrolyte injection, formation, and secondary sealing. The tensile strength of the fluorine-free separator in the length direction of the positive electrode sheet or the negative electrode sheet is 2260 kgf / cm 2 The tensile strength of the fluorine-free separator in the width direction of the positive or negative electrode sheet is 1820kgf / cm 2 The peeling force between the fluorine-free separator and the positive electrode sheet is 10.2N / m, and the peeling force between the fluorine-free separator and the negative electrode sheet is 19.6N / m.
[0131] In the above preparation method, the following method can be used to obtain relevant parameters.
[0132] The tensile strength of the fluorine-free diaphragm can be obtained by the following method: cut the fluorine-free diaphragm into small strips of 15mm±0.2mm along the parallel length direction and parallel width direction, use the WD-D3 electronic universal testing machine, with a gap of 50mm between the upper and lower clamps, clamp the two ends of the foil in the clamps respectively, and start the test at a speed of 100mm / min until the diaphragm breaks, the equipment stops testing, and the breaking strength σm and σt are recorded. The error of the test is no more than 10% for 3 times, and the average value is taken. σm represents the tensile strength of the diaphragm along the parallel length direction, and σt represents the tensile strength of the diaphragm along the parallel width direction, and the unit is kgf / cm 2 .
[0133] The peeling force between the fluorine-free diaphragm and the electrode can be obtained by the following method: disassemble the battery after formation, cut the electrode with the fluorine-free diaphragm on the surface into small strips of 15mm±0.2mm, use the WD-D3 electronic universal testing machine, clamp the diaphragm with the upper fixture and the electrode with the lower fixture, peel 30mm, record the peeling strength, and calculate the average value. The peeling force between the fluorine-free diaphragm and the positive electrode is Tc, and the peeling force between the fluorine-free diaphragm and the negative electrode is Ta, the unit is N / m.
[0134] The cross-sectional sample of the fluorine-free diaphragm can be prepared by ion milling equipment, and the thickness of the base film can be tested under SEM.
[0135] The tensile strength of the current collector can be obtained by the following method: cut the foil into small strips of 15mm±0.2mm, use the WD-D3 electronic universal testing machine, with a gap of 50mm between the upper and lower clamps, clamp the two ends of the foil in the clamps respectively, and start the test at a speed of 10 and 50mm / min for the aluminum foil and copper foil respectively until the foil breaks and the equipment stops testing, and record the fracture strength σ. The error of the test is no more than 10% for 3 times, and the average value is taken. σa represents the tensile strength of the negative electrode current collector, and σc represents the tensile strength of the positive electrode current collector.
[0136] The porosity can be obtained by the following method: cut the electrode or fluorine-free diaphragm with an area greater than 0.1㎡ or a weight greater than 3g, measure the thickness of the cut electrode or fluorine-free diaphragm, and record the thickness data. Put the sample into the sample cup after folding, use the true density meter to test the real volume V0 of the sample, calculate the apparent volume V1 of the sample = measured electrode thickness * electrode length * electrode width, and the sample porosity = (V1-V0) / V1*100%.
[0137] The relevant parameters of other embodiments and comparative examples are shown in Table 1.1, Table 2.1, Table 3.1 and Table 4.1.
[0138] Test Case
[0139] 1. Battery cycle capacity retention rate at 25°C
[0140] Test method: Cycle at 25℃, charge at 1C to cut-off voltage, charge at constant voltage to 0.05C cut-off current, discharge at 1C to lower limit voltage, repeat the above charge and discharge steps 200 times. The maximum discharge capacity of the first 3 cycles is recorded as R1, the discharge capacity of 200 cycles is recorded as R2, and the capacity retention rate is calculated as R2 / R1*100%.
[0141] 2. Battery cycle expansion rate at 25°C
[0142] Test method: Cycle at 25°C, charge at 1C to the cut-off voltage, charge at constant voltage to 0.05C cut-off current, discharge at 1C to the lower limit voltage, and repeat the above charge and discharge steps 200 times. The initial fully charged thickness of the battery cell is recorded as W1, and the thickness of the fully charged battery cell after 200 cycles is recorded as W2. The expansion rate is calculated as (W2-W1) / W1*100%.
[0143] 3. Battery charge and discharge at 25℃
[0144] Test method: 1. Charge and discharge at 0.5C for one cycle, record the discharge capacity R0; 2. Charge at 2C to the cut-off voltage, record the charge capacity R3, charge at constant voltage to 0.05C cut-off current, record the charge capacity R4, discharge at 0.5C to 3V; 3. Charge at 0.5C to the upper limit of voltage, charge at constant voltage to 0.05C, discharge at 2C to the lower limit of voltage, record the discharge capacity R5. The charging constant current ratio is R3 / (R3+R4), and the discharging constant current ratio is R5 / R0.
[0145] 4. 130℃ full electric furnace temperature
[0146] Test method: Fully charge the battery, place it in a thermostat, heat it from room temperature to 130°C at a rate of 5°C / min, and keep it warm for 1 hour after reaching 130°C. Observe whether the battery cell catches fire or explodes.
[0147] The data in the above embodiments and comparative examples are shown in Table 1.1, Table 2.1, Table 3.1 and Table 4.1, and the test results are shown in Table 4.2.
[0148] Table 1.1
[0149]
[0150]
[0151] Table 2.1
[0152] Example Tc Ta σc σa σc / Tc+σa / Ta Example 1 10.2 19.6 180 430 39.6 Example 2-1 10.2 19.6 220 430 43.5 Example 2-2 10.2 19.6 83 430 30.1 Example 2-3 10.2 19.6 180 550 45.7 Embodiment 2-4 10.2 19.6 180 340 35.0 Embodiment 2-5 20 25 180 430 26.2 Embodiment 2-6 7 9 180 430 73.5
[0153] Table 3.1
[0154] Example H0 Ka K Ks Ka / (H0+4*Ks) Kc / (H0+4*Ks) Example 1 5 32.5% 24.7% 43.90% 0.048 0.037 Example 3-1 5 39.0% 31.0% 43.90% 0.058 0.046 Example 3-2 5 21.0% 19.0% 43.90% 0.031 0.028 Example 3-3 9 32.5% 24.7% 43.90% 0.030 0.023 Embodiment 3-4 5 32.5% 24.7% 36.60% 0.050 0.038 Embodiment 3-5 5 32.5% 24.7% 50.20% 0.046 0.035 Comparative Example 4 5 50.2% 46.7% 55.30% 0.070 0.065
[0155] Table 4.1
[0156] Example H0 H1 F0 F1 F0 / (H0+2*H1) F1 / (H0+2*H1) Example 1 5 2 2 2 0.22 0.22 Example 4-1 5 1 2 2 0.29 0.29 Example 4-2 5 2 3 3 0.33 0.33 Comparative Example 5 5 0 2 2 0.40 0.40 Comparative Example 6 16 2 2 2 0.10 0.10
[0157] Table 4.2
[0158]
[0159]
[0160] The following conclusions can be drawn from the analysis of Tables 1.1 to 4.1:
[0161] 1) Compared with Comparative Examples 1 to 4, in Example 1 and Example 1-1 to Example 1-6, by limiting the tensile strength of the fluorine-free diaphragm and the bonding force between the fluorine-free diaphragm and the electrode, the battery can obtain a good cycle life, charge rate and good high temperature stability, and can well inhibit cycle expansion, thereby achieving a balance of various battery performances.
[0162] 2) By comparing Example 1 with Example 1-1 and Example 1-2, it can be seen that the tensile strength of the fluorine-free diaphragm in Example 1-1 is higher, the tensile strength of the fluorine-free diaphragm in Example 1-2 is lower, and the cycle life and charging rate of Example 1 are between Example 1-1 and Example 1-2.
[0163] 3) By comparing Example 1 with Examples 1-3 to 1-6, it can be seen that increasing or decreasing the peeling force between the positive electrode sheet, the negative electrode sheet and the fluorine-free separator on the basis of Example 1 will affect the cycle life and charging rate of the battery.
[0164] 4) By comparing Example 1 with Examples 2-1 to 2-6, it can be seen that by reasonably configuring the bonding force between the fluorine-free diaphragm and the electrode piece and the tensile strength of the electrode piece, the battery can be restrained to prevent the battery from lateral extension, thereby achieving a balance in the various performances of the battery.
[0165] 5) By comparing Example 1 with Examples 3-1 to 3-5, it can be seen that by reasonably configuring the relationship between the porosity of the electrode, the thickness of the base film and the porosity of the fluorine-free diaphragm, a reasonable balance is achieved between the porosity of the electrode and the porosity of the fluorine-free diaphragm, so that the battery has good electrolyte permeability and ion transmission capacity, which can improve the overall performance of the battery.
[0166] 6) By comparing Example 1 and Example 3-1, it can be seen that by increasing the porosity of the positive electrode sheet and the negative electrode sheet, the overall performance of the battery is reduced.
[0167] 7) By comparing Example 1 with Examples 3-5, it can be seen that the charge and discharge rate of the battery can be improved by increasing the porosity of the fluorine-free diaphragm.
[0168] 8) By comparing Example 1 with Example 4-1, Example 4-2, Comparative Example 5 and Comparative Example 6, it can be seen that by configuring the relationship between the thickness of the base film and the ceramic layer, the size of the negative electrode sheet and the size of the separator, the high temperature stability of the battery can be improved and furnace temperature failure can be avoided.
[0169] 9) By comparing Example 1 and Example 4-1, it can be seen that the overall performance of the battery can be improved by reducing the thickness of the ceramic layer, which is manifested in an increase in cycle life, a decrease in cycle expansion, and an increase in charge and discharge rate.
[0170] 10) By comparing Example 1 and Example 4-2, it can be seen that by improving F0 and F1 on the basis of Example 1, the overall performance of the battery is affected to a certain extent.
[0171] In the description of the present application, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present application.
[0172] In the description of the present application, it should be understood that the terms "including" and "having" and any variations thereof used in the embodiments of the present application are intended to cover non-exclusive inclusions. For example, a process, method, system, product or apparatus comprising a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or apparatuses.
[0173] Unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed", etc. should be understood in a broad sense, for example, it can be a fixed connection, it can also be a detachable connection, or it can be integrated; it can be directly connected, or it can be indirectly connected through an intermediate medium, it can make the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to the specific circumstances. In addition, the terms "first", "second", etc. are used for descriptive purposes only and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated.
[0174] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A battery, characterized in that: include: Positive electrode; Negative electrode; and a fluorine-free diaphragm, the fluorine-free diaphragm comprising a base film and adhesive layers formed on both sides of the base film, the adhesive layers comprising an adhesive agent that does not contain fluorine, The tensile strength of the fluorine-free diaphragm in the length direction is σm, the tensile strength of the fluorine-free diaphragm in the width direction is σt, the peeling force between the fluorine-free diaphragm and the positive electrode sheet is Tc, the peeling force between the fluorine-free diaphragm and the negative electrode sheet is Ta, and the σm, the σt, the Tc, and the Ta satisfy the relationship: 80≤(σm+σt) / Tc≤800; 120≤(σm+σt) / Ta≤900.
2. The battery according to claim 1, characterized in that The σm, the σt, the Tc, and the Ta satisfy the relationship: 100≤(σm+σt) / Tc≤440; 130≤(σm+σt) / Ta≤500.
3. The battery according to claim 1, characterized in that The σm=1100kgf / cm 2 ~3000kgf / cm 2 ; And / or, said σt=1000kgf / cm 2 ~3000kgf / cm 2 ; And / or, Tc=6N / m-30N / m; And / or, Ta=6N / m~30N / m.
4. The battery according to claim 3, characterized in that The σm=1800kgf / cm 2 ~2800kgf / cm 2 ; And / or, said σt=1800kgf / cm 2 ~28000kgf / cm 2 ; And / or, Tc=8N / m-20N / m; And / or, Ta=8N / m~15N / m.
5. The battery according to claim 1, characterized in that The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer, and the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer. The tensile strength of the positive electrode current collector is σc, and the tensile strength of the negative electrode current collector is σa. The σc and σa satisfy the relationship: 20≤σc / Tc+σa / Ta≤75.
6. The battery according to claim 5, characterized in that The σc=90N / m~260N / m, preferably, the σc=110N / m~230N / m; And / or, the σa=300N / m~800N / m, preferably, the σa=350N / m~550N / m.
7. The battery according to claim 1, characterized in that The thickness of the base film is H0, the porosity of the fluorine-free separator is Ks, the porosity of the positive electrode sheet is Kc, the porosity of the negative electrode sheet is Ka, and H0, Ks, Kc, and Ka satisfy the relationship: 0.028≤Ka / (H0+4*Ks)≤0.066; 0.022≤Kc / (H0+4*Ks)≤0.
062.
8. The battery according to claim 7, characterized in that The H0=4um~15um, preferably, the H0=4um~9um; And / or, Ks=24% to 52%, preferably, Ks=34% to 45%; And / or, Kc=14% to 44%, preferably, Kc=22% to 37%; And / or, the Ka=19%-48%, preferably, the Ka=25%-38%.
9. The battery according to claim 1, characterized in that The thickness of the base film is H0, the fluorine-free separator further comprises a ceramic layer disposed on at least one side of the base film, the thickness of the ceramic layer is H1, the negative electrode sheet extends upwardly from the positive electrode sheet in width, and the length of the negative electrode sheet extending from the positive electrode sheet is F0, the fluorine-free separator extends from the negative electrode sheet in the width direction, and the length of the fluorine-free separator extending from the negative electrode sheet is F1, and H0, H1, F0, and F1 satisfy the relationship: 0.18≤F0 / (H0+2*H1)≤0.38; 0.18≤F1 / (H0+2*H1)≤0.
38.
10. The battery according to claim 9, characterized in that The H0=4um~15um, preferably, the H0=4um~9um; And / or, H1=0.5 μm to 3 μm; And / or, F0=1 μm to 4 μm; And / or, F1=1 μm to 4 μm.
11. The battery according to any one of claims 1 to 10, characterized in that The adhesive layer is selected from one or more of polyethylene oxide, polyacrylonitrile, polymethyl methacrylate, polyvinyl butyral, polydopamine, polyimide, and polystyrene-acrylate.
12. An electrical equipment, characterized in that: A battery comprising the battery according to any one of claims 1 to 11.
Citation Information
Patent Citations
Electrochemical device and electric equipment
CN114614200A
Battery diaphragm, preparation method thereof and battery
CN116454542A